LEGAL STRATEGIES IN OVERCOMING OVERCLAIMS ON SKINCARE PRODUCTS: BPOM POLICY EVALUATION - Widyawati, Rachel Luna; Widodo, J. Priyanto (Sabtida, 2025)
Skincare products have become an important part of the cosmetic industry, but the practice of overclaiming in marketing is increasingly common. Overclaiming occurs when manufacturers state the benefits of a product without being supported by adequate scientific evidence, which can mislead consumers. This study aims to analyze the effectiveness of regulations implemented by the Food and Drug Supervisory Agency (BPOM) in overcoming overclaiming in skincare products. The method used is a normative legal approach with regulatory analysis and literature studies related to BPOM policies. The results of the study show that BPOM has implemented various regulations, including BPOM Regulation Number 23 of 2019 concerning Technical Instructions for Cosmetic Product Claims and Law Number 8 of 1999 concerning Consumer Protection. However, the implementation of regulations still faces challenges, especially in supervising products on e-commerce platforms and social media. The legal strategies implemented by BPOM include pre-market and post-market supervision, but their effectiveness still needs to be improved. This study recommends increasing digital supervision, consumer education, and stricter sanctions for violators of regulations so that consumer protection can be more optimal.